Fea design and implementation of double spring shape memory alloys actuator - Ascic, Maida (My University, 2018)
Bu çalışma, NiTiNol (Nikel-Titanyum) bazlı şekil hafızalı alaşımın süperelastik mekanik özelliklerinden yararlanarak bir şekil hafızalı yayının analitik ve sonlu elemanlar modelerini sunmaktadır. Şekil hafızalı alaşımların endüstriyel uygulamaları sürekli olarak arttığından, hangi şartlar altında, hangişekilde ve hangi bölümlerde arıza yapılabileceğini ve hangi yüklerin dayanabileceğini anlamak için iyi bir simülasyon modeline ihtiyaç vardır. Mühendislik uygulamasında, analiz büyük ölçüde sonlu eleman bilgisayar programlarının kullanımı ile gerçekleştirilir.Sonlu elemanlar analizinde doğru model simülasyonların yapılması çok önemlidir ve bu çalışmada önerilen modelin sistem tasarım sürecini kolaylaştıracağına ve bu süreçlerin minimize edeceğine inanılmaktadır.Tasarım sürecinden sonra bu yay, akım, yük ve yer değiştirme değerlerini ölçebilen deney düzeneği kullanılarak test edilir. Deney düzeneğinde yay ağırlık ile deformasyona uğrar ve elektrik akımı ile ısınarak orijinal şekline geri döner.

This study presents a finite element and analytical modelling of a shape memory spring by taking advantages of the superelastic mechanical properties of shape memory alloy based on NiTiNol (Nickel-Titanium Alloy). Because industrial applications of shape memory alloys are constantly increasing, there is a need for good simulation models to understand whether, under what conditions, and in which ways a part could fail and what loads it can withstand. In engineering practice, analysis is largely performed with the use of finite element computer programs.It is very important to make the simulations with correct model in Finite Element Analysis and it is believed that the model which is proposed in this study will facilitate the system design process and that these processes will be minimized.After design process this spring is tested using an experimental setup which is capable of measuring current, load and displacement values. In experimental setup spring undergoes deformation with weight effect and it returns to original shape by heating with electrical current.
Keywords: Actuator; Aktüatör; Biçim hafızalı alaşımlar; Finite Element Analysis; Mechatronics; Mekatronik; Shape memory alloys; Sonlu elemanlar analizi; Spring; Şekil hafızalı metaller; Titaniım; Titanyum; Yay Shape Memory Alloys